First synthesis of silicon nanocrystals in amorphous silicon nitride from a preceramic polymer. (3rd April 2019) - Biesuz, M; Bettotti, P; Signorini, S; Bortolotti, M; Campostrini, R; Bahri, M; Ersen, O; Speranza, G; Lale, A; Bernard, S; Sorarù, G D
Abstract: We report the first synthesis of silicon nanocrystals embedded in a silicon nitride matrix through a direct pyrolysis of a preceramic polymer (perhydropolysilazane). Structural analysis carried out by XRD, XPS, Raman and TEM reveals the formation of silicon quantum dots and correlates the microstructures with the annealing temperature. The photoluminescence of the nanocomposites was investigated by both linear and nonlinear measurements. Furthermore we demonstrate an enhanced chemical resistance of the nitride matrix, compared to the typical oxide one, in both strongly acidic and basic environments. The proposed synthesis via polymer pyrolysis is a striking innovation potentially allowing a mass-scale production nitride embedded Si nanocrystals.